Modeling the Defense-Growth Nexus in a Post-Conflict Country - A Piecewise Linear Approach - Gerhard Reitschuler; Ludger J. Löning (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2004)
The defense-growth nexus is investigated empirically using longitudinal data for Guatemala and allowing the effect of defense spending on growth to be nonlinear. Using recently developed econometric methods involving threshold regressions, evidence of a level-dependent effect of military expenditure on GDP growth is found: a positive and significant externality effect of defense spending prevails for relatively low levels of defense spending and becomes negative, albeit insignificant, for higher levels.
Keywords: E13; C22; H56; 330; Guatemala; defense expenditures; nonlinearity; economic growth; externality effect; Militärausgaben; Wirtschaftswachstum; Externer Effekt; Bürgerkrieg; Schätzung; Guatemala